Decentralized voltage control of distributed generation using a distribution system structural MIMO model. (February 2016) - Di Fazio, Anna Rita; Fusco, Giuseppe; Russo, Mario
Abstract: The voltage control problem in Low Voltage (LV) distribution systems is becoming increasingly important due to the presence of Distributed Generation (DG). Recently, DG units have been proposed to contribute to voltage control according to a Volt/Var law which does not realize regulation. Moreover, since the existing LV systems are operated in a decentralized way without communication links, the simultaneous response of the controllers of the DG units may result into operational conflicts and instability. To overcome these problems, the present paper illustrates a design methodology for decentralized voltage controllers that act on DG reactive power injections. The controllers are suitable for the LV systems since they ensure voltage regulation and stability by using only local measurements and without information exchanges. The design is based on a proposed structural MIMO model of the distribution system. Robust stability is also analyzed: changes in the operating conditions of the distribution system are modeled as unstructured additive uncertainties affecting the MIMO model. A case study gives evidence of the applicability of the proposed design; the performance of the controllers in terms of both stability and regulation of the nodal voltages of three DG units connected to a LV distribution feeder is tested by numerical simulations; finally, a comparison with a Volt/Var technique is performed. Abstract : Highlights: Decentralized voltage controllers acting on DG reactive powers in LV distribution systems. Development of a MIMO model of distribution systems with DG suitable for the design. Design of decentralized voltage controllers of DG units without data exchange. Stability analysis in the presence of model uncertainties representing variable operating conditions. Support to the LV feeder voltage profile without conflicts among the DG controllers.